Implementasi Konsep “Evangelion” pada Desain Interior Youth Catholic Center di Surabaya - Laurent Saviour Ekaprabhana; Ronald Hasudungan Irianto Sitindjak; Stephanie Melinda Frans (Intra, 2019)
An apparent decrease in youth Catholic’s attendance to church is a phenomenon that happens in the western hemisphere, which becomes a notable case in Church’s growth in this present time.  This will not conceal the probability of occurrence in Indonesia’s youth Catholics’ growth, especially in Surabaya. Catholic youths need a ‘vessel’ for means of growing their faith and self-discovery as a Catholic. Youth Catholic Center (YCC)’s interior design with the concept “Evangelion” is expected to be a space for Catholic youths to grow in their respective faith. Combining technology and education which are integrated with YCC’s facilities, this design helps Catholic youths who are still in doubt to partake in activities with communities through a fun and modern approach. The presence of YCC’s interior space helps increase relations between Catholic youths by means of an interactive and communicative method. YCC is regarded to be Catholic youths’ means of growing their love in God, Catholicism, and social life, which takes reference from Five Marks of the Church.